Integrated molecular and serological survey of Rhodococcus equi in horses from three regions of Kazakhstan - Zanilabdin, Makpal; Ilgekbayeva, Gulnaz; Otarbayev, Bauyrzhan; Nissanova, Raikhan; Mussayeva, Gulzhan; Takai, Shinji; Suzuki, Yasunori; Kakuda, Tsutomu; Kurman, Serikzhan; Kassymov, Yerken; Valiyeva, Bayan (Frontiers in Veterinary Science, 2025)
IntroductionRhodococcus equi is a facultative intracellular pathogen causing bronchopneumonia in foals; data from Central Asia are limited. We conducted a cross-sectional serological and molecular survey in horses from three regions of Kazakhstan (Kyzylorda, Almaty, Akmola).MethodsSera from 312 animals (272 adults, 40 foals) on 20 farms were tested by indirect ELISA. Selected clinical samples underwent culture, PCR, and 16S rRNA sequencing.ResultsOverall seroprevalence was 8.3% (26/312; 95% CI 5.8–11.9). Positivity among foals was 25.0% (10/40; 95% CI 14.2–40.2) versus 5.9% (16/272; 95% CI 3.7–9.3) in adults, with farm-level clusters observed in the Almaty region. R. equi was isolated from three foals; a representative sequence was deposited (GenBank OP448586).DiscussionPhylogenetic analysis placed the Kazakhstani isolate within a clade of equine-associated R. equi strains reported from Europe and East Asia (>99.5% identity). We provide molecularly confirmed evidence of R. equi circulation in horses from three regions of Kazakhstan, with higher seropositivity in foals and focal farm-level clustering. Findings support the need for broader geographic sampling, test validation against reference sera, and incorporation of management/risk-factor data. Limitations include the regional scope, small number of foals, and absence of environmental or human sampling.